UNDERSTANDING THE DYNAMICS OF SPORT TOURISM ON ISLANDS: CHALLENGES AND STRATEGIC PLANNING FROM EVENT ORGANIZERS’ PERSPECTIVES - Ku Azmi, Nuwal Fadhilah; Hanafiah, Mohd Hafiz; Md Zain, Nur Adilah; Mior Shariffuddin, Nur Shahirah (PLANNING MALAYSIA, 2024)
This study explores the challenges event organizers face in managing sporting events on island destinations and highlights the need for strategic planning to address unique logistical and operational issues. The qualitative research was conducted through semi-structured interviews with selected Malaysian sporting event organizers. The study found that the available tourism ecosystem, favorable destination image, accessibility, and sporting facilities availability are the key elements a sports tourism destination must have and are preferred by event organizers. In terms of challenges, organizing sporting events on islands involves overcoming logistical constraints, environmental impacts, high costs, and the need for cultural sensitivity, emphasizing careful planning and local engagement. The study's findings illuminate the importance of a comprehensive understanding of the tourism ecosystem, destination image, accessibility, and sporting facilities in shaping a thriving sports tourism destination in an island setting.